KINETIKA FERMENTASI ASAM LAKTAT DARI TEPUNG SORGUM MENGGUNAKAN YEAST DAN L.Plantarum - Istianah, Nur; Gunawan, Setyo (Jurnal Rekayasa Bahan Alam dan Energi Berkelanjutan, 2017)
Sorghum fermentation was introduced by three of microbes which are dry baker’s yeast, L.Plantarum and the combination of them. Fermentor was operated at 37°C for 72 hrs. Inoculation of microbes was held after incubation period of  3-4 hrs. Those fermentation produce the different lactic acid and pH(p<0.05). L.Plantarum produced the highest lactic acid which was followed by pH changes.  This fermentation gave the highest lactic acid yield of 85.01%(w/w) at cell yield of 0.14%(w/w). The production rate of fermentation by L.Plantarum was 0.306 g.h-1, maximum specific growth rate 1.5689 g.h-1, and Monod constat at 13.3262.